Fire versus grazing as tools to restore serpentine grasslands under global change. (18th March 2021) - Hernández, Eliza; Shaw, E. Ashley; Aoyama, Lina; Brambila, Alejandro; Niederer, Christal; Weiss, Stuart B.; Hallett, Lauren M.
Abstract : Grassland restoration in a world of change—including nitrogen deposition and invasion—requires solutions that can be sustained and effective in the face of novel drivers. This challenge is amplified in systems characterized by high spatiotemporal variability, as management to address novel drivers may affect a system differently across its range of variability. California serpentine grasslands epitomize this challenge: they host a high diversity of native species, are characterized by temporal and spatial variability, and are experiencing atmospheric nitrogen deposition that leads to a conversion from native annual forbs to non‐native annual grasses. Here, we test the interactive effects of grazing and fire to restore native serpentine species following annual grass invasion and litter accumulation. We assess management outcomes (burned‐grazed, burned‐ungrazed, and unburned‐ungrazed) using a long‐term (2004–2012) monitoring dataset. A 2004 wildfire led to a reduction in annual grasses and a transient increase in native species (forb) richness. In 2008, cattle grazing was reintroduced and crossed with the burn legacy, which sustained post‐fire diversity and eventually led to native recovery in unburned areas, with a caveat that a period of high precipitation promoted the growth of annual grasses. Our study indicates that short‐term management, such as fire, can promote native forb recovery in invaded serpentine grassland communities, but that ongoing treatments like grazing are necessary to maintain restoration outcomes. We speculate that this recovery may be due to the presence of a robust native seed bank, which may persist despite a period of annual grass conversion.